Performance of Dye-Sensitized Solar Cell with Carrot-Based Dyes in Deep Eutectic Solvent and KI/I2 Electrolytes - Pasigon, Christzon Pagdawan (Trends in Sciences, 2025)
Dye-sensitized solar cells (DSSCs) offer a potential alternative to the conventional silicon-based photovoltaic cells due to their low cost and the wide choice of materials available. Their efficiency and stability, however, greatly depend on the photosensitizer and electrolyte materials. In the study, the possibility of carrot roots and leaves as natural photosensitizers with the combination of Deep Eutectic Solvent (DES) and KI/I2 electrolytes on DSSC performance was explored. Among the treatments, Treatment 3 (DES with carrot roots) exhibited the highest performance, with an Isc of 0.0042 A, Voc of 1.2 V, and an overall efficiency (η) of 3.53 %. This performance is attributed to DES’s ability to enhance charge transport and minimize recombination losses. Treatment 1 (DES with carrot leaves) also demonstrated favorable results, achieving an efficiency of 2.5 %, attributed to the effectiveness of DES in stabilizing natural dyes. In contrast, Treatment 2 (KI/I2 with carrot leaves) displayed a reduced efficiency of 1.43 %. Meanwhile, Treatment 4 (KI/I2 with carrot roots) recorded the lowest efficiency of 0.68 %, suggesting that KI/I2 electrolyte limits charge transfer in natural dye-based DSSCs. Conductivity measurements supported these findings, with Treatment 3 exhibiting the highest conductivity (3.50×10−4 Ω⁻¹⋅m⁻¹) and the lowest resistance (285.71 Ω), followed by Treatment 1. Conversely, Treatments 2 and 4 exhibited higher resistance values, correlating with their lower photovoltaic performance. Additionally, dark current analysis demonstrated that DES-based treatments exhibited lower current leakage over time, reinforcing their potential for long-term stability. Conclusively, these results have demonstrated the potential of DES-based electrolytes in improving natural photosensitizer efficiencies in DSSCs and provide evidence for designing a more effective and stable solar cell. Moreover, it contributes to the development of renewable energy in which natural materials of low cost are combined with DES to develop green solar technologies as an alternative to fossil fuels. HIGHLIGHTS The study proves that DSSCs with the use of DES-based electrolytes have higher efficiency and heat resistance than KI/I2 DES treatments yielded efficiencies of 3.53 %, with enhanced charge transportation and low recombination loss. The DES-based electrolytes maintain stable open-circuit voltage (Voc) and charge transport at varying temperatures. This suggests DES as a promising alternative for improving DSSC stability under fluctuating environmental conditions. Carrot leaf extracts, rich in carotenoids and chlorophyll, were explored as eco-friendly photosensitizers. While carotenoids contributed to efficient light absorption and electron transfer, chlorophylls showed lower efficiency, suggesting the potential for optimizing natural dye combinations for DSSCs. GRAPHICAL ABSTRACT